2005
DOI: 10.1002/bit.20499
|View full text |Cite
|
Sign up to set email alerts
|

Engineering mammalian cell factories for improved recombinant monoclonal antibody production: lessons from nature?

Abstract: In this review we consider how cell specific recombinant monoclonal antibody (Mab) production by engineered mammalian cells can be improved. Whilst it is generally recognized that Mab production is limited post-transcriptionally at folding and assembly reactions, genetic engineering strategies based on overexpression of individual chaperones or foldases in mammalian cells have not reliably increased cell specific Mab production. Given that recent studies have established that chaperones and foldases themselves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(75 citation statements)
references
References 134 publications
(105 reference statements)
0
72
0
3
Order By: Relevance
“…At the transition from the exponential to the stationary cell culture phase cell growth slowed down and RVGP Considering optimizations for the synthesis of heterologous recombinant protein by genetically modified cell populations, the easiest approach of favouring the cell multiplication in view of obtaining high levels of recombinant cell product may not be always the indicated one. A rational approach would be to somehow drive the cell metabolism redirecting cell resources used for cell proliferation to the recombinant protein expression (Palomares et al 2004;Dinnis and James 2005).…”
Section: Discussionmentioning
confidence: 99%
“…At the transition from the exponential to the stationary cell culture phase cell growth slowed down and RVGP Considering optimizations for the synthesis of heterologous recombinant protein by genetically modified cell populations, the easiest approach of favouring the cell multiplication in view of obtaining high levels of recombinant cell product may not be always the indicated one. A rational approach would be to somehow drive the cell metabolism redirecting cell resources used for cell proliferation to the recombinant protein expression (Palomares et al 2004;Dinnis and James 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative Western blot confirmed that BsAbs were efficiently secreted and that the lower product yields were not due to retention in the endoplasmic reticulum via cellular mechanisms such as the unfolded protein response (results not shown). [54][55][56][57] Targeted binding Binding activity was maintained for both EGFR and LPS targets for all engineered BsAb formats ( Table 2; Fig. 2).…”
Section: Production and Yieldmentioning
confidence: 93%
“…LCs are critical for the proper folding of HCs in ER, and the amount of free LCs in culture media is related to its productivity. [27][28][29][30][31][32] Although the production of LCs is reportedly related to the quality (aggregate content) of mAb, 33,34) the analyses in these study were conducted under conditions in which the productivity was intentionally lowered. Because these conditions have little relevance to those in which therapeutic mAbs are actually produced, it is important to analyze the effects of LCs on quality under conditions in which the cell selection process is actually performed.…”
Section: Characterization Of Antibody Aggregatesmentioning
confidence: 99%